2020
DOI: 10.3389/fnbeh.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Shared Vulnerability to Post-traumatic Stress Disorder and Substance Use Disorders

Abstract: Psychoactive substance use is a nearly universal human behavior, but a significant minority of people who use addictive substances will go on to develop an addictive disorder. Similarly, though ∼90% of people experience traumatic events in their lifetime, only ∼10% ever develop post-traumatic stress disorder (PTSD). Substance use disorders (SUD) and PTSD are highly comorbid, occurring in the same individual far more often than would be predicted by chance given the respective prevalence of each disorder. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 370 publications
(393 reference statements)
3
40
0
3
Order By: Relevance
“…At the same time, dealing with a mental disorder may also contribute to the formation of particular stressors (or complication of those already existing), by interfering with functional impairment, often observed across various mental disorders. Behaviors surrounding drug seeking, drug use, or addiction can increase individuals' risk of witnessing or experiencing traumatic stressors (e.g., violence, overdose death) ( 91 ), or generate stressors in the form of interpersonal conflict, legal consequences, or employment or financial instability.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, dealing with a mental disorder may also contribute to the formation of particular stressors (or complication of those already existing), by interfering with functional impairment, often observed across various mental disorders. Behaviors surrounding drug seeking, drug use, or addiction can increase individuals' risk of witnessing or experiencing traumatic stressors (e.g., violence, overdose death) ( 91 ), or generate stressors in the form of interpersonal conflict, legal consequences, or employment or financial instability.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD symptom severity positively correlates with risk-taking behaviors, including thrill seeking and risky sexual behaviors. 86 88 Notably, PTSD is also highly comorbid with substance abuse: 80 , 89 92 According to the American Addiction Center, 50–66% of PTSD-sufferers have comorbid substance abuse issues. According to the European Monitoring Centre for Drugs and Drug Addiction, depression—a disorder highly defined by its reward-system deficits—has the highest substance abuse comorbidity prevalence of all psychiatric disorders.…”
Section: Ptsd and External Reward Seekingmentioning
confidence: 99%
“…Clinical observations, case reports and epidemiological studies first suggested high rates of comorbidity between PTSD and substance use disorders (SUD), prompting translational research examining the possibility of overlapping neural mechanisms. Many studies have demonstrated a high comorbidity of PTSD with drug addiction in both clinical and community samples[ 38 , 39 ]. Approximately 36% to 50% of those that meet criteria for SUD also meet criteria for lifetime PTSD, and those with PTSD predictably have a history of drug abuse or dependence[ 40 ].…”
Section: Comorbidity Of Ptsd and Substance Use Disordersmentioning
confidence: 99%